HDAC6-selective inhibitor CAY10603 ameliorates cigarette smoke-induced small airway remodeling by regulating epithelial barrier dysfunction and reversing - Qin Zhang; Liming Yan; Ye Lu; Xiaodong Liu; Yan Yin; Qiuyue Wang; Xiu Gu; Xiaoming Zhou (Respiratory Research, 2024)
Abstract Background Small airway remodelling is a vital characteristic of chronic obstructive pulmonary disease (COPD), which is mainly caused by epithelial barrier dysfunction and epithelial-mesenchymal transition (EMT). Recent studies have indicated that histone deacetylase 6 (HDAC6) plays an important role in the dysregulation of epithelial function. In this study, we investigated the therapeutic effects and underlying mechanisms of an inhibitor with high selectivity for HDAC6 in COPD. Methods Cigarette smoke (CS) exposure was used to establish a CS-induced COPD mouse model. CAY10603 at doses of 2.5 and 10 mg/kg was injected intraperitoneally on alternate days. The protective effects of CAY10603 against CS-induced emphysema, epithelial barrier function and small airway remodeling were evaluated using hematoxylin and eosin (H&E) staining, Masson’s trichrome staining, immunohistochemical staining, and western blot. The human lung bronchial epithelial cell line (HBE) was used to elucidate the underlying molecular mechanism of action of CAY10603. Results HDAC6 levels in the lung homogenates of CS-exposed mice were higher than that those in control mice. Compared to the CS group, the mean linear intercept (MLI) of the CAY10603 treatment group decreased and the mean alveolar number (MAN)increased. Collagen deposition was reduced in groups treated with CAY10603. The expression of α-SMA was markedly upregulated in the CS group, which was reversed by CAY10603 treatment. Conversely, E-cadherin expression in the CS group was further downregulated, which was reversed by CAY10603 treatment. CAY10603 affects the tight junction protein expression of ZO-1 and occludin. ZO-1 and occludin expression were markedly downregulated in the CS group. After CAY10603treatment, the protein expression level of ZO-1 and occludin increased significantly. In HBE cells, Cigarette smoke extract (CSE) increased HDAC6 levels. CAY10603 significantly attenuated the release of TGF-β1 induced by CSE. CAY10603 significantly increased the E-cadherin levels in TGF-β1 treated HBE cells, while concurrently attenuated α-SMA expression. This effect was achieved through the suppression of Smad2 and Smad3 phosphorylation. CAY10603 also inhibited TGF-β1 induced cell migration. Conclusions These findings suggested that CAY10603 inhibited CS induced small airway remodelling by regulating epithelial barrier dysfunction and reversing EMT via the TGF-β1/Smad2/3 signalling pathway.